Immunomodulatory Properties of Vitamin D in Children - L.V. Kvashnina (Zaslavsky O.Yu., 2013)
The paper presents the data of the literature showing the immunomodulatory properties of vitamin D, and the results of studies that indicated an increased risk and incidence of various respiratory infections when it is deficient in children.